Effects on bacon quality of feeding increasing glycerol and dried distillers grains with solubles to finishing pigs - Goehring, B.L.; Houser, Terry A.; DeRouchey, Joel M.; Hunt, Melvin C.; Tokach, Michael D.; Dritz, Steven S.; Gerlach, B.M.; Goodband, Robert D.; Nelssen, Jim L.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 84 barrows (PIC 337 × 1050, initially 68.3 lb) were fed a corn-soybean meal-based diet with added dried distillers grains with solubles (DDGS; 0 or 20%) and increasing glycerol (0, 2.5, or 5%) to determine the effects on belly quality. Criteria that were evaluated included: belly length, thickness, firmness, and slice yield; proximate and fatty acid analyses; iodine values; and sensory characteristics. There were no (P > 0.08) DDGS × glycerol interactions on any criteria measured. Inclusion of 20% DDGS in the diet decreased belly firmness (P < 0.04), as measured by the belly flop test (fat-side down method). Twenty percent DDGS decreased (P < 0.01) the percentage of myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, vaccenic acid, total saturated fatty acids, and total monounsaturated fatty acids. In contrast, 20% DDGS increased (P < 0.01) the percentage of linoleic acid, α-linolenic acid, eicosadienoic acid, total polyunsaturated fatty acids, unsaturated:saturated fatty acid ratios, polyunsaturated:saturated fatty acid ratios, and iodine values. The inclusion of 0, 2.5, and 5% glycerol in swine diets did not affect any measured criteria in this study. In conclusion, feeding DDGS at a level of 20% decreased belly firmness and changed the fatty acid profile; however, it did not affect belly processing or sensory characteristics. Glycerol fed at 2.5 or 5.0% did not affect belly quality, fatty acid profile, or sensory characteristics of bacon.
Keywords: Swine; Belly quality; Dried distiller grains with solubles; Glycerol